Efectos educativos de la fecundidad adolescente: Evidencia causal a partir de la legalización del aborto en Uruguay - María Laura Alzúa; Cecilia Velázquez (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2018)
– There is a strong gap in school enrollment rates between young girls with and without children in Uruguay. This paper aims to explain if this gap responds to a cause-effect relationship, identifying the impact of becoming a teen mother on the educational outcomes of young girls. Our identification strategy takes advantage of a reform in Uruguay allowing voluntary termination of pregnancy since December 2012. This reform made Uruguay the only Latin-American country - except from Cuba, Guyana and Mexico City - where abortion on demand is legal. However, the supply of legal abortion services faced several drawbacks in some geographical areas where a high share of gynecologists refused to induce abortions, since the law protects the right to exercise 'conscientious objection' with respect to abortion. Thus, the supply of abortion services varied substantially across departments. Differences in the timing and degree of implementation provide a source of identification for estimating the causal effect of teenage fertility on education using an Instrumental Variables approach. Local abortion rates - carried out under the new legal framework - are used to instrument teenage fertility rates. This is the first study to have official information on the number of legally terminated pregnancies in Uruguay since abortion reform in 2012. Results suggest that access to legal abortion reduced teenage fertility. We provide an exogenous instrument for teenage fertility - legal abortion rates - and this is one of the main contributions of the paper. Second-stage results indicate the causal effect of teenage fertility on educational attainment is null for the group of compliers. This suggests that poor educational performance of teenage mothers cannot be attributed to early motherhood per se, but to pre-existing disadvantages.
Keywords: I21; J13; 330; Teenage fertility; Abortion; Education; Instrumental Variables; Latin America; Uruguay